Pengaruh corporate governance terhadap penghindaran pajak - Emanuel Claritus; Norman Duma Sitinjak; Harmono Harmono (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
This study aims to examine the effect of corporate governance on tax avoidance in property and real estate companies listed on the Indonesian stock exchange by comparing tax avoidance that occurred before the pandemic (2018-2019) and during the pandemic (2020-2021). The data used in this research is secondary data. Sampling used Purpose sampling and obtained a sample of 14 companies with an observation period of 4 years. Data were processed using SPSS with multiple linear regression. From the results of the research analysis, it shows that institutional ownership and the board of commissioners before the pandemic and during the pandemic had no effect on tax evasion, managerial ownership before the pandemic had no effect on tax evasion while during the pandemic managerial ownership had a negative effect on tax evasion, and the audit committee before the pandemic had an effect positive on tax evasion while during the pandemic the audit committee had no effect on tax evasion.